Antifungal Activity of the Unsaponifiable Fraction of the Fixed Oils of Trichosanthes Seeds - Harit*, Meena; Rathee, P.S. (Asian Journal of Chemistry, 2012)
In the present note, antifungal activity of the unsaponifiable fraction of the fixed oils of Trichosanthes seeds is studied.